1981
DOI: 10.1177/29.5.6166664
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of structural preservation and immunocytochemical staining in low temperature embedded pancreatic tissue.

Abstract: The recently developed low temperature embedding procedure with the resin Lowicryl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
269
1
2

Year Published

1984
1984
2006
2006

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 699 publications
(279 citation statements)
references
References 17 publications
7
269
1
2
Order By: Relevance
“…The fixatives used in this study, glutaraldehyde alone or followed by osmic acid, preserved fine structure and permitted immunostaining. Although evidence has shown that post-fixation with osmic acid reduces antigenicity severely (Roth et al, 1981;Bendayan, 1982), this effect seems to be reversed by the etching of Lowicryl and Araldite sections.…”
Section: Discussionmentioning
confidence: 99%
“…The fixatives used in this study, glutaraldehyde alone or followed by osmic acid, preserved fine structure and permitted immunostaining. Although evidence has shown that post-fixation with osmic acid reduces antigenicity severely (Roth et al, 1981;Bendayan, 1982), this effect seems to be reversed by the etching of Lowicryl and Araldite sections.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the chemical reactivity of the cured resin, its method of curing and the degree of crosslinking are important parameters (Causton, 1984). Acrylate resins, such as Lowicryl K4M (Roth et al, 1981;Armbruster et al, 1982Armbruster et al, , 1983Carlemalm et al , 1982Carlemalm et al , , 1985Altman et al, 1984;Kellenberger et al, 1987) and LR White (Newman et al, 1982(Newman et al, , 1983aCraig and Miller, 1984;Newman and Jasani, 1984;Newman and Hobot, 1987), have some advantages for postembedding staining over epoxy resins. They are hydrophilic and tolerate water during polymerization, hence dehydration of specimens need not be so stringent.…”
Section: Postembedding Labelling Proceduresmentioning
confidence: 99%
“…They were then chemically fixed (at 4 mC for at least 1 h) in PBS (10 mM sodium phosphate, 137 mM sodium chloride, pH 7n0) with 0n2% (w\v) formaldehyde and 0n3% (w\v) glutaraldehyde and washed twice in the same buffer containing 10 mM glycine. Lowicryl K4M resin was used for embedding the cells (Gerberding & Mayer, 1988 ;Roth et al, 1981). Sections were cut with an Ultracut E (Reichert-Jung) ultramicrotome, mounted on nickel grids and kept, face down, on drops of PBS until they were immunolabelled.…”
Section: Methodsmentioning
confidence: 99%